Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Berpikir Kritis Siswa Pendidikan Agama Kristen dan Budi Pekerti Kelas XI SMA Negeri 1 Raya Tahun Pembelajaran 2024/2025 - Anggi Clarita Situmeang; Pestaria Naibaho; Senida Harefa; Sudirman Lase; Damayanti Nababan (Jurnal Teologi Injili dan Pendidikan Agama, 2024)
The aim of this research is to determine the effect of critical thinking skills using the guided inquiry learning model. The research hypothesis is: "There is an influence on the critical thinking abilities of class XI students at SMA Negeri 1 Raya in the 2024/2025 academic year before and after using the guided inquiry learning model. The population is the entire class The research sample was determined using purposive sampling, namely 35 students in class XI IPS 2 as the experimental class using the guided inquiry learning model and 35 students in class This research method uses the Quasy Experimental Design method using the Nonequivalent Control Design Group. The instrument used in this research was a 30 item questionnaire. Research data for the questionnaire was analyzed using the average difference test formula (N-Gain Score). It was found that the average value for the experimental class was 0.7454 in the high category. And the average value for the control class is 0.1481, which is in the low category. Then carrying out an independent test using the t test obtained a value of tcount = 15.168 > ttable((a=0.05;df=68) = 2.000. Thus it can be concluded that the research hypothesis is accepted, namely that there is an influence on the critical thinking abilities of class XI students at SMA Negeri 1 Raya Academic Year 2024/2025 before and after using the guided inquiry learning model.